2020
DOI: 10.1002/jha2.52
|View full text |Cite
|
Sign up to set email alerts
|

High percentage of smudge cells in a patient with COVID19: Rediscovering their utility

Abstract: We present a patient with SARS‐CoV‐2 infection, with an unexpected presence of lymphocytosis. Examination of blood film revealed mature small lymphocytes associated with high percentage of smudge cells (63%). A peripheral flow cyometry evidenced a CD5 negative CLL. A high percentage of smudge cells is associated with CLL diagnosis and has an important prognostic value: better survival and prolonged time to first treatment. It is a useful index in developing countries with low access to molecular testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…Increased levels of MCP were reported before and linked to unfavorable outcomes secondary to the monocyte activation 2 , 64 . Similar fluctuation of the cytokines was reported before in blood samples obtained from COVID-19 3 , 5 , 35 , 63 65 . The universal presence of MUC-16 is somewhat puzzling, except that this marker has utility in guiding fluid replacement in heart failure 66 , 67 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Increased levels of MCP were reported before and linked to unfavorable outcomes secondary to the monocyte activation 2 , 64 . Similar fluctuation of the cytokines was reported before in blood samples obtained from COVID-19 3 , 5 , 35 , 63 65 . The universal presence of MUC-16 is somewhat puzzling, except that this marker has utility in guiding fluid replacement in heart failure 66 , 67 .…”
Section: Discussionsupporting
confidence: 87%
“…Our immunological profiling revealed that urine CCL23, CXCL13, IL-15, CD5, several members of the TNFαR family, and monocyte chemoattractant protein correlated with blood levels. Prior studies indicated that these molecules are an essential component of the immunological response in COVID-19 and other viral infections 3 , 5 , 7 , 8 , 28 , 56 , 60 , 63 . Though the dynamics of the investigated biomarkers seem to be less exaggerated as compared to blood levels, they were related to increased mortality, organ failure, and unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. that smudge cells are seen in COVID-19 patients [12]. These features are consistent with the findings of leukoerythroblastic reaction.…”
Section: Mis-a Is a Complication Of Sars-cov-2 Infectionsupporting
confidence: 90%
“…Some of the data, however, are consistent with the mechanistic understanding proposed for this case. The median age for diagnosis of CLL is 72, and two of the cases, like the case presented herein, were unusually young at 49 and 55 years of age, consistent with (though far from diagnostic of) the concept of early unmasking due to an infectious trigger [ 7 , 9 ]. The case presented by Largeaud et al’s study was of an 83-year-old gentleman, but the authors provided evidence of a normal WBC count both one year before and at the time of admission, lymphocytosis with studies diagnostic of CLL on day 11 of admission, and subsequent resolution of lymphocytosis 5 months after discharge although the CLL clone was still detectable [ 10 ].…”
Section: Discussionsupporting
confidence: 74%